The initiation; and, The captive. Part I - Smith, L. J. (Lisa J.); Smith, L. J. (Lisa J.). (New York : HarperTeen, 2008)
Cassie is drawn into the Secret Circle, a coven of young witches whose power has controlled New Salem for three hundred years, and when she falls hopelessly in love with the leader's boyfriend, she is tempted to use dark powers.
Works originally published separately: New York : Harper Paperbacks, 1992.
Keywords: Witchcraft -- Fiction; Love -- Fiction; Paranormal fiction; Love stories